Pengaruh Kebersihan Lingkungan terhadap Minat Kunjungan Wisatawan di Kawasan Wisata Alam Lembah Harau Kanagarian Tarantang Kecamatan Harau Kabupaten Lima Puluh Kota - Fitria Nopita; Monalisa Febrianti; Muhammad Farhan Arazi; Rahmayani Kurnia Sari; Sastri Darmitha; Syarifah Habibah Humairoh; Yulia Indah Simbolon; Yoskar Kadarisman; Dian Kurnia Anggreta; Mardhatillah Mardhatillah (Pusat Riset dan Inovasi Nasional, 2026)
Environmental cleanliness is a critical factor in the effective management of nature-based tourist destinations, as it strongly shapes tourists’ perceptions of destination quality, comfort, and overall attractiveness, as well as their intention to visit and revisit. This study aims to examine the extent to which environmental cleanliness influences tourists’ visit intention in the Harau Valley tourism area (Lembah Harau), Kanagarian Tarantang, Harau District, Lima Puluh Kota Regency. The research employed a quantitative survey method by distributing structured questionnaires to 50 tourists during their visit to Lembah Harau. The variables measured include tourists’ perceptions of environmental cleanliness, such as waste management practices, sanitation conditions, and the availability of waste disposal facilities, as well as visit intention indicators, including intention to return and willingness to recommend the destination to others. The findings highlight the importance of maintaining a clean environment to enhance tourists’ positive behavioral intentions. The implications of these findings suggest that destination managers and local government authorities should consistently enforce cleanliness policies, strengthen integrated waste management systems, and provide adequate sanitation facilities to enhance the attractiveness of Lembah Harau and support sustainable tourism development, without neglecting the need for continuous monitoring, evaluation, and improvement in these areas.